PENGEMBANGAN GAME EDUKASI ANAMATCH (ANAGRAM AND MATCH UP) BERBASIS WORDWALL UNTUK PENGENALAN KOSAKATA BAHASA INGGRIS ANAK KELOMPOK B DI TK ISLAM NURUL IMAN SEKARBELA - Chiyara Novi; Nuriadi; Ika Rachmayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a Wordwall-based Anamatch (Anagram and Match Up) Educational Game to help group B children at Nurul Iman Sekarbela Islamic Kindergarten in introducing English vocabulary appropriately, practically, and effectively. This game is expected to increase children's interest in learning and ability to introduce English vocabulary in a fun and effective way. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 21 children of group B Melon. Data collection techniques used observation, documentation, and questionnaires. The results showed that the developed educational game obtained a media expert validation percentage of 94.5% and a material expert validation of 95.2% with a very appropriate category. Teacher responses obtained a percentage of 96.6% with a very practical category. The results of the effectiveness test showed an increase in children's English vocabulary recognition ability from 72% in trial I with the category of Developing According to Expectations (BSH) to 93% in trial II with the category of Developing Very Well (BSB). The N-Gain Score calculation yielded a value of 0.763, with a percentage of 76.33%, which is considered high. Therefore, the Anamatch (Anagram and Match Up) Wordwall-based educational game is deemed feasible, practical, and effective for introducing English vocabulary to group B children.